122 Guanylyl cyclase C as a target for CAR-T cell therapy in a metastatic gastric cancer model. (9th November 2020) - Lisby, Amanda; Baybutt, Trevor; Weindorfer, Megan; Carlson, Robert; Zalewski, Alicja; Waldman, Scott; Snook, Adam
Abstract : Background: Gastric cancer is the sixth most common cancer and second-leading cause of cancer-related mortality worldwide. 1 The heterogenous and genetically complex nature of this disease underlies the challenges in developing effective therapies for metastatic gastric cancer. In the majority of cases, stomach tumors evolve from intestinal metaplasia resulting in ectopic expression of the enterocyte differentiation antigen guanylyl cyclase C (GUCY2C) by 50% of primary and metastatic gastric cancers. 2–4 In the context of the efficacy of GUCY2C-directed chimeric antigen receptor (CAR)-T cells against metastatic colorectal cancer in animal models, 5, 6 we hypothesized that this adoptive cell therapy may be effective against metastatic gastric cancer. Methods: Here, we explored the efficacy of GUCY2C-directed CAR-T cells for gastric cancer in a patient derived xenograft (PDX) tumor model. Also, we interrogated translational GUCY2C biomarker assays using RT-qPCR, immunoblot analysis, and immunohistochemistry (IHC) for the intended purpose of identifying patients whose tumors express GUCY2C and could benefit from GUCY2C-directed CAR-T cell therapy. Results: GUCY2C-directed CAR-T cells significantly reduced subcutaneous T84 colorectal tumor growth, producing a 5-fold reduction in tumor volume, compared to control treated tumors. GUCY2C-directed CAR-T cells produced no response in tumors produced from the GUCY2C-deficient colorectal cancer cell line, SW480. Importantly, GUCY2C-directed CAR-T cells controlled gastric cancer PDX growth, maintaining a >12-fold reduction in tumor volume compared to control and in some cases produced complete tumor elimination. Furthermore, IHC based assays, indicate that antibodies developed in our laboratory may be suitable for development of a companion diagnostic for GUCY2C-directed CAR-T cells. Indeed, the commercial polyclonal antibody demonstrated robust, non-specific staining regardless of tissue type or GUCY2C mRNA profile, while novel monoclonal antibodies produced in our laboratory primarily detected protein localized to the membrane of glandular epithelial cells, demonstrating antigen specificity, and indicating their potential for further development in diagnostic companion assays to identify gastric cancer patients who may benefit from GUCY2C-directed CAR-T cell therapy. Conclusions: GUCY2C-directed CAR-T cells prevented the growth of, and at times eliminated, a subcutaneous gastric cancer PDX model. In the context of previously established safety in mouse models, additional studies defining the efficacy of GUCY2C-directed CAR-T cells in gastric cancer models may allow future translation of this therapy to patients with advanced gastric cancers. Concurrent development of a novel companion diagnostic IHC assay would permit identification of the 50% of gastric cancer patients whose tumors express GUCY2C and could benefit from this therapy. Acknowledgements: This work was supported by a DeGregorio Family Foundation Award and by the Department of Defense Congressionally Directed Medical Research Programs (W81XWH-17-1-0299, W81XWH-191-0263, and W81XWH-19-1-0067) to AES. SAW is supported by the National Institutes of Health (NIH) (R01 CA204881, R01 CA206026, and P30 CA56036), the Defense Congressionally Directed Medical Research Program W81XWH-17-PRCRP-TTSA, and Targeted Diagnostic & Therapeutics. SAW and AES were also supported by a grant from The Courtney Ann Diacont Memorial Foundation. SAW is the Samuel M.V. Hamilton Professor of Thomas Jefferson University. AZ was supported by NIH institutional award T32 GM008562 for Postdoctoral Training in Clinical Pharmacology.The authors thank the NCI Patient-Derived Models Repository for their support and resources to make this research possible. The authors also thank the Sidney Kimmel Cancer Center Translational Research & Pathology Core Facility, and the Office of Animal Resources at Thomas Jefferson University for their continued technical assistance and support in this research. Ethics Approval: This study was approved by the Thomas Jefferson University Institutional Review Board (#14.0204) and the Instituational Animal Care and Use Commitee (Protocol #01529). References: Bray F, Ferlay J, Soerjomataram I, Siegel RL, Torre LA, Jemal A. Global cancer statistics 2018: GLOBOCAN estimates of incidence and mortality worldwide for 36 cancers in 185 countries. CA Cancer J Clin 2018;68:394–424. doi:10.3322/caac.21492. Park J, Schulz S, Haaf J, Kairys JC, Waldman SA. Ectopic expression of guanylyl cyclase C in adenocarcinomas of the esophagus and stomach. Cancer Epidemiol Biomarkers Prev 2002;11:739–44. Birbe R, Palazzo JP, Walters R, Weinberg D, Schulz S, Waldman SA. Guanylyl cyclase C is a marker of intestinal metaplasia, dysplasia, and adenocarcinoma of the gastrointestinal tract. Hum Pathol . 2005;36:170–9. doi:10.1016/j.humpath.2004.12.002. Mathur D, Root AR, Bugaj-Gaweda B, Bisulco S, Tan X, Fang W, et al. A Novel GUCY2C-CD3 T-Cell Engaging Bispecific Construct (PF-07062119) for the Treatment of Gastrointestinal Cancers. Clin Cancer Res 2020;26:2188–202. doi:10.1158/1078-0432.CCR-19-3275. Magee MS, Kraft CL, Abraham TS, Baybutt TR, Marszalowicz GP, Li P, et al. GUCY2C-directed CAR-T cells oppose colorectal cancer metastases without autoimmunity. Oncoimmunology 2016;5:e1227897. doi:10.1080/2162402X.2016.1227897. Magee MS, Abraham TS, Baybutt TR, Flickinger JC, Ridge NA, Marszalowicz GP, et al. Human GUCY2C-Targeted Chimeric Antigen Receptor (CAR)-Expressing T Cells Eliminate Colorectal Cancer Metastases. Cancer Immunol Res 2018;6:509–16. doi:10.1158/2326-6066.CIR-16-0362.